1995
DOI: 10.1007/bf00220882
|View full text |Cite
|
Sign up to set email alerts
|

DNA amplification fingerprinting analysis of bermudagrass (Cynodon): genetic relationships between species and interspecific crosses

Abstract: We have used DNA amplification fingerprinting (DAF) to study the genetic variation of bermudagrass (Cynodon) species and cultivars of interspecific crosses that exhibit leaf-blade textural characteristics ranging from coarse to fine. Arbitrary octamer primers produced complex and reproducible amplification profiles with high levels of polymorphic DNA. Phylogenetic analysis using parsimony (PAUP) and unweighted pair group cluster analysis using arithmetic means (UPGMA) grouped 13 bermudagrass cultivars into sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…DNA amplification fingerprinting (DAF) is a method that uses arbitrary oligonucleotide primers to detect polymorphisms among closely related organisms (Caetano-Anollés and Bassam 1993; Caetano-Anollés et al 1995). DNA amplification fingerprinting and arbitrary signatures from amplification profiles (ASAP) were used to assess the genetic stability of both Tifgreen and Tifdwarf.…”
Section: The Genetic Instability Of Commercial Cultivars Leading To Omentioning
confidence: 99%
See 1 more Smart Citation
“…DNA amplification fingerprinting (DAF) is a method that uses arbitrary oligonucleotide primers to detect polymorphisms among closely related organisms (Caetano-Anollés and Bassam 1993; Caetano-Anollés et al 1995). DNA amplification fingerprinting and arbitrary signatures from amplification profiles (ASAP) were used to assess the genetic stability of both Tifgreen and Tifdwarf.…”
Section: The Genetic Instability Of Commercial Cultivars Leading To Omentioning
confidence: 99%
“…Dendrograms were generated from an unweighted pair group cluster analysis using arithmetic means (UPGMA) and phylogenetic analysis using parsimony (PAUP). DNA amplification fingerprinting revealed differences between Tifgreen and Tifdwarf with five polymorphisms present among three primer sequences; however, the UPGMA and PAUP analyses demonstrated that the two cultivars were very closely related (Caetano-Anollés et al 1995). Farsani et al (2012) were able to use inter-simple sequence repeat markers and a UPGMA clustering method to place Tifgreen and Tifdwarf into separate subgroups under the same cluster.…”
Section: Genetic Diversity Among Bermudagrass Cultivars Used On Puttimentioning
confidence: 99%
“…A number of researchers have employed randomly amplified polymorphic DNA (Iqbal et al, 2008;Zhang et al, 2011;Huo et al, 2013) and DNA amplified fingerprinting procedures (Caetano-Anollés et al, 1995, 1997Karaca et al, 2002;Zhang et al, 2013). Recently, the amplified fragment length polymorphism (AFLP) DNA method (Vos et al, 1995) has been used to detect genetic diversity among forage bermudagrass cultivars (Karaca et al, 2002), to quantify the genetic variation of Cynodon transvaalensis and its relatedness to hexaploid C. dactylon var.…”
Section: Introductionmentioning
confidence: 99%
“…Different DNA markers have been used in studies of genetic diversity, relatedness, phylogeny, and in identifying off-types of Cynodon cultivars . DNA amplification fingerprinting (DAF) [9] has been used to study relatedness of some genotypes (clonal plants) of C. transvaalensis , C. dactylon , and hybrid derivatives of the two species [10,11], detect off-types originating from sod contamination instead of somatic mutation, and to identify the cultivars Tifway, Tifgreen, and Tifdwarf [12], Furthermore, DAF has been used to examine the relatedness of 18 Cynodon cultivars found in Australia [13], to assess genetic relatedness among 62 Cynodon accessions representing eight species [14], to assess the genetic relatedness of 17 seed-propagated turf-bermudagrass cultivars [15], and to determine the degree of genetic relatedness of Chinese cultivars with the existing vegetative cultivars commonly grown in the United States [16]. Randomly amplified polymorphic DNA (RAPD) [17] was used to evaluate diversity of 75 C. dactylon accessions collected from different regions of Iran [18].…”
Section: Introductionmentioning
confidence: 99%